Cloning and characterization of a protective outer membrane lipoprotein of Actinobacillus pleuropneumoniae serotype 5. - Bunka, S (1995)
The gene encoding an outer membrane lipoprotein (omlA) of Actinobacillus pleuropneumoniae serotype 5 was cloned, and the protein was expressed in Escherichia coli. One open reading frame of 1,104 bp was detected that encoded a protein (OmlA) with a predicted molecular mass of 40 kDa. A comparison with the omlA gene and the corresponding protein of A. pleuropneumoniae serotype 1 (G.-F. Gerlach, C. Anderson, S. Klashinsky, A. Rossi-Kampos, A.A. Potter, and P.J. Wilson, Infect. Immun. 61:565-572, 1993) revealed that the nucleic acid sequences had an overall sequence identity of 62.9% and the deduced amino acid sequences showed a sequence agreement of 57.3%. Both proteins were antigenically distinct. In a Western blot (immunoblot) analysis using a specific antiserum against A. pleuropneumoniae serotype 5 OmlA, a homologous protein was detected in the reference strains of A. pleuropneumoniae serotypes 5A, 5B, and 10. Pigs immunized with this recombinant protein were protected from death in an aerosol challenge experiment with an A. pleuropneumoniae serotype 5 isolate.